Research of lipid exchange diffusion of medium-age patients with chronic pancreatitis with diabetes mellitus - L. S. Babinets; N. A. Shevchenko; H. N. Sasyk; O. S. Zemlyak (Kazimierz Wielki University, 2017)
Chronic pancreatitis refers to diseases in which both excretoric and incretoric sections of the pancreas are damaged, which in later stages leads to the development of concomitant diabetes mellitus (DM), which are not sufficiently studied in this pathology. This article presents a study of lipid metabolism in patients with chronic middle-aged pancreatitis with concomitant diabetes. It has been proved that the presence of DM significantly complicated the clinical course of chronic pancreatitis (CP) in the ballistic system M - ANNHEIM, which correlated with changes in the program (r=0,67; p<0,001), the criteria for ultrasound (r=0,54; p<0,01), the level of glycosylated hemoglobin (r=0,66; p<0,001). In patients with CP with concomitant diabetes the severity of the disease was more pronounced than in patients with CP: the average severity (C) predominated in 69,56% of patients in group 2, with 26,32% of the 1st, and cases of severe and severe severity. A direct reliable correlation between all the atherogenic indicators of the lipidogram and the age of the patients and the duration of the course of the CP were found, which makes it possible to assume the age and duration of the CP by factors of the deepening of the dyslipidemia. In patients with CP in combination with DM and dyslipidemia, the lower index of fecal α-elastase level was established in comparison with the CP group: (157,15 ± 7,36) versus (112,86 ± 2,98), respectively (p<0,001) which proved a deepening of dyslipidemia in the development of excretory insufficiency of the pancreas.